KAJIAN HUKUM TERHADAP KEPUTUSAN PEJABAT TATA USAHA NEGARA ATAS PENERBITAN SERTIFIKAT HAK MILIK YANG CACAT HUKUM BERDASARKAN PUTUSAN PTUN NO. 10. G/ PTUN. 2019-MDN - MASLON HUTABALIAN; MARIA FERBA ADITYA (JURNAL JUSTIQA, 2022)
Law is a tool in a country to regulate the joints of state life such as life between one legal subject and another legal subject, both in Public Law and Private Law. This research was conducted to answer the problem, namely how to study the law of a state administrative decision that is legally flawed, the case study of PTUN No.10/G/2019/PTUN-MDN and how is the legal responsibility of state administrative officials for a decision that is legally flawed. By using descriptive normative research method consisting of research on legal observations and research on legal effectiveness. The results of this study state that a state administrative decision that is legally flawed such as a SHM with legal defects, both physical and juridical data should not occur due to negligence or intentional negligence of state administrative officials, because such problems cause conflicts and losses in the community, also have lost trust. the public towards government services and the actions of state administrative officials who are negligent or intentionally commit unlawful acts in this case issuing a certificate of ownership of a plot of land that is not based on the applicable laws and regulations, then the official, both on his position and personally, can be held accountable at the before the law and can be prosecuted criminally or civilly